MicroRNA‐124‐3p attenuates the development of nerve injury–induced neuropathic pain by targeting early growth response 1 in the dorsal root ganglia and spinal dorsal horn. Issue 4 (20th June 2021) - Jiang, Mingjun; Zhang, Xuan; Wang, Xueli; Xu, Feng; Zhang, Jian; Li, Liren; Xie, Xiaohang; Wang, Li; Yang, Yin; Xu, Ji‐Tian
Abstract: Emerging evidence indicates the early growth response 1 (Egr1) plays an important role in the pathogenesis of chronic pain. However, the regulation of Egr1 expression in the DRG and spinal cord in neuropathic pain remains unclear. In the current study, the neuropathic pain was conducted by lumber 5 spinal nerve ligation (SNL) in rats. The role of miR‐124‐3p in Egr1 expression was examined. Our results showed that the SNL led to a significant increase in the expression of Egr1 mRNA and protein in the DRG and dorsal horn. This increased expression of Egr1 correlated with a reduction of miR‐124‐3p in the same region. Prior i.t. injection of Egr1 decoy AYX1 inhibited the expression of Egr1 and attenuated the neuropathic pain‐like hypersensitivity following SNL. The dual‐luciferase reporter assay revealed the luciferase activity of the Egr1 3′‐UTR plasmid was inhibited by the miR‐124‐3p agomir. But this inhibition was completely reversed in the mutant 3′‐UTR Egr1 group. In vivo, the SNL‐induced behavioral signs of neuropathic pain and the increases in Egr1 mRNA and protein in the DRG and dorsal horn were prevented by prior to i.t. injection of miR‐124‐3p agomir. While, i.t. injection of miR‐124‐3p antagomir in naïve rats resulted in mechanical allodynia and thermal hyperalgesia and an overexpression of Egr1 in the DRG and dorsal horn. Together, our results suggest that the miR‐124‐3p‐regulated Egr1 expression in the DRG and dorsal horn contributes to the development of neuropathic pain. Targeting miR‐124‐3p might be a promising therapeutic strategy in the treatment of chronic pain. Abstract : The Egr1 has been implicated in regulating a variety of genes' expression. MicroRNAs (MiRNAs) have emerged as key regulators in the maladaptive plasticity of chronic pain. However, whether miRNA‐124 involves in the modulation of Egr1 expression in neuropathic pain remains elusive. In the current study, we found the spinal nerve injury‐induced down‐regulation of miR‐124‐3p via promoting Egr1 expression in the dorsal root ganglion (DRG) and the spinal dorsal horn contributed to the development of neuropathic pain. Targeting DRG and spinal miR‐124‐3p might be a promising therapeutic strategy for the prevention and treatment of chronic pain.